2017
DOI: 10.2351/1.4983758
|View full text |Cite
|
Sign up to set email alerts
|

Multipass laser hot-wire welding: Morphology and process robustness

Abstract: There are great prospects for utilizing multipass laser hot-wire welding to join thick steel sheets, especially for techniques commonly performed in single passes, e.g., laser arc hybrid welding, fall short, presenting great opportunities for vehicle industries and offshore applications. Many modern approaches for applying these techniques rely on customized wire feeding nozzles or special scanner optics to ensure proper laser–wire interactions and, in turn, robust process behavior, making them less accessible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In welding, Engström et al (2001) and others have shown that laser-arc hybrid techniques can be highly capable competitors to their single heat source counterparts. Näsström et al (2017) showed that excellent surface morphology of welds can be produced using laser hybrid processes and suggests that laser positioning can be used to affect the attained bead shape. An arc technique that has been shown to introduce significant benefits to GMAW is cold metal transfer (CMT).…”
Section: Introductionmentioning
confidence: 99%
“…In welding, Engström et al (2001) and others have shown that laser-arc hybrid techniques can be highly capable competitors to their single heat source counterparts. Näsström et al (2017) showed that excellent surface morphology of welds can be produced using laser hybrid processes and suggests that laser positioning can be used to affect the attained bead shape. An arc technique that has been shown to introduce significant benefits to GMAW is cold metal transfer (CMT).…”
Section: Introductionmentioning
confidence: 99%
“…6, 7) and hot-wire laser welding (HWLW) (Refs. 5,8,9) have been developed to improve the welding performance. Feeding an additional wire could increase the gap tolerance (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding an additional wire could increase the gap tolerance (Ref. 8) and modify the chemical composition and weld metal microstructure (Ref. 5).…”
Section: Introductionmentioning
confidence: 99%
“…The materials investigated range from mild steels [15], stainless steels [10], aluminum alloys [3], or nickel-based alloys [17]. Fiber and disk lasers with maximum powers up to 16 kW are most frequently used for the development.…”
Section: Introductionmentioning
confidence: 99%